Adverse childhood experiences and labour market inactivity among young women: a population-based study - Harpa S. Eyjólfsdóttir; Marín Dögg Bjarnadóttir; Hilda Björk Daníelsdóttir; Arna Hauksdottir; Edda Bjork Thordardottir; Thor Aspelund; Unnur A. Valdimarsdóttir (BMC Public Health, 2026)
Abstract Background Young people not in employment, education, or training (NEET) are a major concern presenting extensive societal and personal costs. Adverse childhood experiences (ACEs) can have longstanding harmful effects on health, education and employment participation. This study examined if ACEs are associated with NEET status among young Icelandic women, and whether perceived coping ability and social support moderate this relationship. Methods Using data from 6 101 women aged 18–29 in the Stress-And-Gene-Analysis cohort, NEET status was self-reported, ACEs were assessed with the ACE-International Questionnaire (13 items), current perceived coping ability with the Connor-Davidson Resilience Scale and social support with the Multidimensional Scale of Perceived Social Support. Logistic regression estimated associations between ACEs (total score, categorical score, and individual subtypes) and NEET status. Moderation by perceived coping ability and social support was assessed using interaction models, with effects evaluated on the absolute scale using predicted probabilities and differences in predicted NEET probability across ACE levels. Multiple imputation addressed missing data. Results After adjustment for sociodemographic factors, ACEs were strongly associated with NEET in a dose-dependent manner. Compared with women having 0 ACEs, women with ≥ 5 ACEs had almost sixfold higher odds of NEET (OR 5.62 [95% CI 3.60–8.78]), and each additional ACE increased odds by 23% (OR 1.23 [1.18–1.29]). When examined separately, all ACE subtypes—especially emotional neglect, emotional abuse, mental illness in the household and bullying—were associated with NEET. Analyses of predictive probabilities indicated that the association between ACEs and NEET was stronger among women with low coping ability, whereas social support did not modify this association. Conclusions ACEs are strongly associated with NEET status among young women with low coping ability exacerbating the association, while social support showed no modifying effect. This suggests deep-rooted impacts of childhood adversity may depend more on internal adaptive capacity than on external social resources, highlighting coping capacity as potential target for intervention.